Predicting the unseen: nutritional interventions as a key to combat frailty - Shi, Luya; Tian, Xijiang; Bongsook, Yih; Chen, Jiameng (Frontiers in Nutrition, 2025)
BackgroundFrailty and malnutrition have emerged as critical public health issues amidst global population aging. Malnutrition not only significantly contributes to frailty but also intensifies its clinical symptoms, severely affecting the quality of life and health outcomes in older adults. Research in this field has accelerated in recent years; however, a comprehensive analysis of key research trends and hotspots remains absent. This study employs bibliometric methods to systematically analyze core themes and emerging research directions related to nutritional status and frailty in older adults, identifying potential research frontiers and guiding future development.MethodsA comprehensive search was conducted in the Web of Science Core Collection (WoSCC) database on November 6, 2024, using keywords relevant to frailty and nutrition status in older adults. Bibliometric analyses and knowledge mapping were performed using CiteSpace, VOSviewer, and R software.ResultsBetween 2005 and 2024, 2,357 publications on frailty and nutrition status in older adults were produced by 13,080 researchers from 3,987 institutions across 88 countries. The volume of publications has shown a consistent upward trajectory over the past two decades (R2 = 0.84), with projections indicating a continued increase, peaking at 315 publications by 2033. This sustained growth underscores the field’s significance and ongoing research interest. Early research has centered on the “home-living elderly” demographic, while current investigations have shifted focus from molecular biology, genetics, and health nursing to more clinical and medical domains. Key areas of emphasis now include nutrition and dietetics, geriatrics, oncology, and pharmacology. Emerging research hotspots involve the early identification and management of malnutrition to reduce frailty-related health risks and improve health outcomes and quality of life for older adults. Notable trends include the keywords “prediction,” “nutritional assessment MNA,” “intervention,” and “infection.”ConclusionThis bibliometric analysis offers a comprehensive examination of the research evolution, hotspots, and emerging frontiers in frailty and nutrition status among older adults over the past two decades. The findings provide an objective overview of the academic landscape, offering valuable insights for future research, resource allocation, and policymaking.